5x-1=2(3x+2)

Simple and best practice solution for 5x-1=2(3x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-1=2(3x+2) equation:


Simplifying
5x + -1 = 2(3x + 2)

Reorder the terms:
-1 + 5x = 2(3x + 2)

Reorder the terms:
-1 + 5x = 2(2 + 3x)
-1 + 5x = (2 * 2 + 3x * 2)
-1 + 5x = (4 + 6x)

Solving
-1 + 5x = 4 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-1 + 5x + -6x = 4 + 6x + -6x

Combine like terms: 5x + -6x = -1x
-1 + -1x = 4 + 6x + -6x

Combine like terms: 6x + -6x = 0
-1 + -1x = 4 + 0
-1 + -1x = 4

Add '1' to each side of the equation.
-1 + 1 + -1x = 4 + 1

Combine like terms: -1 + 1 = 0
0 + -1x = 4 + 1
-1x = 4 + 1

Combine like terms: 4 + 1 = 5
-1x = 5

Divide each side by '-1'.
x = -5

Simplifying
x = -5

See similar equations:

| 96-4x=148 | | 7x+5=3x-27 | | t(n)=-5n+2 | | 3d+4=39 | | 4.9(4.9x-4)=-4x+5.3 | | -38=2(4x-3) | | 3(x+4)+8=-7 | | 10x-3.2=-6x+7.2 | | 15=-4(5k-2)+4(1+5k) | | 7x-(2x-18)=58 | | 20-6x=-75-9x | | 4(x-1)-10=-38 | | 3m-2p-4m-p= | | -8c+4v-5= | | W+15-28+5=117 | | 13=7+3u | | 5x+7=-38-6x | | 3log(x)-4log(x+3)+log(y)= | | 9x*2-25y*2=-1 | | 1+4x=1+x | | 5y^2=35 | | -0.8w=5 | | p-24=4(5p-6) | | -38x+76= | | 3ln(x)-4ln(x+3)+ln(y)= | | 5(x+1)=3x(x+4) | | 37-4x=9-8x | | 3ln(x^2)=10 | | -4c-2=19 | | 3lnx^2=10 | | 8+4n=-6(-4-n) | | x^3y-4xy=0 |

Equations solver categories